Hubungan Indeks Massa Tubuh (IMT), Merokok dan Asupan Kafein dengan Kejadian Dispepsia Fungsional pada Mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar - Imtihan, Muhammad; Utama, Lalu Buly Fatrahady; Syuhada, Irwan; Sahrun, Sahrun (Universitas Malahayati, 2025)
ABSTRACT According to WHO (World Health Organization), every year the population of dyspepsia in the world reaches 15-30%. Dyspepsia is discomfort in the upper gastrointestinal tract which is described by a number of symptoms that cause discomfort in the upper abdomen. Some risk factors for functional dyspepsia are triggered by age, gender, stress, caffeinated drinks, alcohol, smoking, consumption of non-steroidal anti-inflammatory drugs (NSAIDs), and body mass index (BMI). This study aims to determine the relationship between body mass index (BMI), smoking, and caffeine intake with the incidence of functional dyspepsia in students of the Faculty of Medicine, Al-Azhar Islamic University. This study uses an approach with a cross-sectional study design. The sampling technique uses purposive sampling. The study was conducted at the Faculty of Medicine, Al-Azhar Islamic University in October 2024. The research sample was 90 respondents. Data were analyzed univariately and bivariately with the Chi-square statistical test. The results of this study showed that there was no significant relationship between body mass index (BMI) and the incidence of functional dyspepsia (p-value 0.709), there was a significant relationship between smoking and the incidence of functional dyspepsia (p-value 0.024), and there was a significant relationship between caffeine intake and the incidence of functional dyspepsia (p-value 0.012). There was no significant relationship between body mass index (BMI) and the incidence of functional dyspepsia in students of the Faculty of Medicine, Al-Azhar Islamic University, and there was a significant relationship between smoking and caffeine intake with the incidence of functional dyspepsia in students of the Faculty of Medicine, Al-Azhar Islamic University. Keywords: Functional Dyspepsia, Body Mass Index, Smoking, Caffeine Intake. ABSTRAK Menurut WHO (World Health Organization), setiap tahun populasi dispepsia di dunia mencapai 15-30%. Dispepsia merupakan ketidaknyamanan pada saluran cerna atas yang digambarkan oleh sejumlah gejala sehingga membuat ketidaknyamanan pada perut bagian atas. Beberapa faktor risiko dispepsia fungsional yaitu dipicu oleh usia, jenis kelamin, stres, minuman berkafein, alkohol, merokok, konsumsi obat anti inflamasi non steroid (OAINS), dan indeks massa tubuh (IMT). Penelitian ini bertujuan untuk mengetahui hubungan indeks masa tubuh (IMT), merokok, dan asupan kafein dengan kejadian dispepsia fungsional pada mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar. Penelitian ini menggunakan pendekatan dengan desain studi cross sectional. Teknik pengambilan sampel menggunakan purposive sampling. Penelitian dilakukan di Fakultas kedokteran Universitas Islam Al-Azhar pada bulan Oktober 2024. Sampel penelitian sebanyak 90 responden. Data dianalisis secara univariat dan bivariat dengan uji statistik Chi-square. Hasil penelitian ini menunjukkan tidak terdapat hubungan yang signifikan antara indeks masa tubuh (IMT) dengan kejadian dispepsia fungsional (p-value 0,709), terdapat hubungan yang signifikan antara merokok dengan kejadian dispepsia fungsional (p-value 0,024), dan terdapat hubungan yang signifikan antara asupan kafein dengan kejadian dispepsia fungsional (p-value 0,012). Tidak terdapat hubungan yang signifikan antara indeks masa tubuh (IMT) dengan kejadian dispepsia fungsional pada mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar, dan terdapat hubungan yang signifikan antara merokok, dan asupan kafein dengan kejadian dispepsia fungsional pada mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar. Kata kunci: Dispepsia Fungsional, Indeks Masa Tubuh, Merokok, Asupan Kafein.